Onion John - Krumgold, Joseph 1908-; Shimin, Symeon 1902-. (New York Crowell, 1959)
His friendship with the town odd-jobs man, Onion John, causes a conflict between Andy and his father.
Keywords: Fathers and sons -- Fiction; Friendship -- Fiction